Effects of psoriasis treatment on genital warts: a case report. (July 2019) - Campoli, Marco; Cinotti, Elisa; Fimiani, Michele; Pellegrino, Michele; Tognetti, Linda; Rubegni, Pietro
The use of immunosuppressive drugs predisposes to infections, as they block the most important stage in antiviral defense, which is the cytotoxic T-lymphocyte HLA-dependent response. We report a case of extensive genital warts in a young woman on therapy for psoriasis with cyclosporine, afterwards successfully treated with an anti-tumor necrosis factor alpha (TNF-α) agent. Cyclosporine may predispose to the reactivation of latent infections and may favor the clinical manifestations of human papillomavirus (HPV)-related diseases, due to the inhibition of cell-mediated immunity that plays a crucial role in controlling HPV infections. In the literature the relationship between HPV and TNF-blockers has not yet been clearly defined. Our case underlines that the prompt interruption of cyclosporine can induce a complete regression of warts without any additional treatment and adds evidence to the possible use of anti-TNF-α in patients with psoriasis and genital warts.